BRANDING POLITIK JOKO WIDODO DALAM PILPRES 2014 DI MEDIA ONLINE - Sun Fatayati (Tribakti: Jurnal Pemikiran Keislaman, 2016)
The presence of the internet has brought new changes in communication behavior. In the real of the political use of the online media occurs by political leaders to construct their personal branding. Construction personal branding become part of political communication with a variety of functions, for political candidates, are expected to influence and attract voters. The purpose of this study is to analyze the construction of the personal branding of Joko Widodo as candidates for Indonesian President 2014-2019, through online medias by making use of news on online medias. Using content analysis method Hsieh & Shannon dengan pendekatan directed content analysis melalui prosedur induksi.. The research findings in the text indicate that Jokowi perform his personal branding construction.